Análisis de la flora vascular de los volcanes del Campo de Calatrava (Ciudad Real, España) - Raúl García-Camacho; César Santamaría; Carlos José Martín-Blanco; María Andrea Carrasco (Anales del Jardín Botánico de Madrid)
We present a study of the vascular flora of the volcanic region of Ciudad Real province, Spain. The flora of the region includes 550 taxa, which correspond to eight volcanoes selected by its different origins and litologies.The taxa pertain to 67 families. The most speciose are Compositae, Leguminosae and Gramineae, which despite of being just 4.48% of the families, include the 35.09% of the species in the catalogue. The best represented chorological group is the Mediterranean s.l., (70% of the taxa). Terophytes conform the predominant biological type (63.45% of the taxa). The study shows that there is not a special flora of volcanic soils in the study area.